Sarcasm Detection using Deep Learning - et. al., Seema Kedar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is becoming a trend in current society to use complex and indirect statements for communication which includes metaphorical language, proverbs and other similar forms. One of such communication form is sarcasm. Sarcastic statements can have symbolized, hidden or even entirely opposite meaning from the conveyed statement. Sarcasm is inherently ambiguous in nature which makes it very difficult to understand even for humans let alone machines. In this paper, we have implemented sarcasm detection based upon difference and similarity between facial emotion of the person and sentiment of his verbally conveyed message.